All-dielectric magnetophotonic gratings for maximum TMOKE enhancement. Issue 9 (16th February 2022) - Carvalho, William O. F.; Mejía-Salazar, J. R.
Abstract : All-dielectric nanophotonic devices are promising candidates for future lossless (bio)sensing and telecommunications applications. Abstract : All-dielectric nanophotonic devices are promising candidates for future lossless (bio)sensing and telecommunication applications. Active all-dielectric magnetophotonic devices, where the optical properties can be controlled by an externally applied magnetic field, have triggered great research interest. However, magneto-optical (MO) effects are still low for applications. Here, we demonstrate a concept for the enhancement of the transverse MO Kerr effect (TMOKE), with amplitudes of up to 1.85, i.e., close to the maximum theoretical values of ±2 (in transmission). Our concept exploits the lateral leaky Bloch-modes to enhance the TMOKE, under near-zero transmittance conditions. Potential applications in (bio)sensing structures are numerically demonstrated. The effects of optical losses were studied using different combinations of materials. Significantly, we demonstrate TMOKE enhancements of two orders of magnitude in relation to recent experimental studies, using the same building materials.